The Impact of Gender Inclusivity On Strategic Foresight - Airene Yasmin, Ratino; Helen Tan, Siew Hong (2023)
Research about the intersection of gender inclusivity and strategic foresight application in a maledominated technological sector is rarely discussed in greater depth. It is widely known that genderinclusive organizations benefit in ways such as increased commitment, enhanced employee confidence, morale and job satisfaction, and an overall improved performance. Strategic foresight, on the other hand, is understood to be beneficial to organizations as it draws useful insights for strategic planning, policymaking, and readiness by anticipating trends, risks, developing issues, potential repercussions, and opportunities. Therefore, the aim of this paper is to highlight the possible approaches to understanding how gender-inclusive organizations may unleash capabilities for strategic foresight especially amongst middle managers. With the emerging number of women in tech, it would be strategic for organizations to leverage on this phenomenon. In addition, a theoretical perspective on the intersection of gender inclusivity and strategic foresight in the technology sectors can contribute towards the discourse on equity and social justice as enshrined in the United Nation SDG 5, namely gender equality and also the principles of ESG. Finally, the elements necessary for organizations to gain a better understanding of gender inclusivity and strategic foresight, some thoughts on future research directions and recommendations are discussed.